Increasing the Economic Independence of Women Farm Workers through Entrepreneurship Training - Fitriliana, Fitriliana; Nasir, Nasir; Hanum, Filia; Ilyas, Ilyas; Marlina, Marlina (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This research aims to increase the economic independence of women farm workers through targeted and applicable entrepreneurship training. The background of this research is based on the low level of income and business skills among female farm workers, which has an impact on their limitations in meeting the economic needs of their families. The method used is a participatory approach with the stages of identifying needs, preparing training materials, implementing training, and evaluating results. The training is focused on developing production skills, business management, marketing, and simple financial management. The results of the study showed that the trainees experienced an increase in knowledge, skills, and motivation to be entrepreneurial. In addition, some participants began to practice the skills acquired to build a small business that contributes to the family's income. These findings indicate that entrepreneurship training can be an effective strategy in increasing the economic independence of women farm workers, while strengthening their role in rural economic development.